The Effect of Lemon Aromatherapy on Reducing the Pain Intensity on Post Sectio Caesarea Patients at Malahayati Islamic Hospital Medan in 2020 - Niasty Lasmy Zaen (Institute of Computer Science (IOCS), 2021)
Sectio Caesarea childbirth can have an impact after the operation, namely the pain. Pain is an unpleasant feeling experienced by post sectio caesarean patients. the pain is gone arise caused by surgery on the abdominal wall and the uterine wall that can’t be lost in one day gives the impact of a mobilization is limited. Various ways can reduce post sectio caesarean of pain, one of them is by giving lemon aromatherapy. This study aims to know if there is an effect of lemon aromatherapy on reducing pain intensity on post-cesarean section patients. This research is a quasi-experimental research with one group pretest and posttest designs. The population in this study were all Post Sectio Caesarea mothers on February 2020 at Rumah Sakit Islam Malahayati Medan were 40 peoples. The sampling technique were carried out by accidental sampling technique so that the number of samples were 28 people. Data analysis used Wilcoxon test. The results of this study indicate that from the pre test results, the majority of respondents had moderate pain are 13 respondents (46.4%), while from the post test results the majority of respondents had mild pain are 12 respondents (42.9%). The results of data analysis showed the value of P = 0.000, where 0.000 <0.05. This case showed that treatment has an effect on reducing pain intensity on post sectio caesarean patients at Rumah Sakit Islam Malahayati Medan in 2020. It was concluded that lemon aromatherapy had an effect on reducing pain intensity on post sectio caesarean patients. For respondents to be able to use lemon aromatherapy to reduce of pain on Post Sectio Caesarea patients as a non-pharmacological method that is safe and easy to apply at home.